Audio description from an easy-to-understand language perspective: A corpus-based study in Catalan - Arias-Badia, Blanca; Matamala, Anna (The Journal of Specialised Translation, 2023)
Providing accessible audiovisual content which caters for diverse user needs is one of the challenges of today’s digitised society. Audio description (AD) has been recently proposed to adopt the principles of easy-to-understand language (E2U) to reach larger audiences (Bernabé-Caro and Orero 2020). A focus group developed in the context of the EASIT project (Arias-Badia and Matamala 2020) showed that some professionals were reluctant to accept easy AD, arguing that AD addresses persons who cannot see, rather than persons who cannot understand. Comments were also made indicating that current audio descriptions may already be easy to understand. Given the lack of research in this area, this article presents results of a corpus study conducted on nine AD scripts in Catalan and provides data on the extent to which current audio descriptions are already “easy” taking into account existing parameters linked to easy-to-understand language principles. The features under analysis are part of speech distribution, sentence complexity, the use of (in)frequent lexicon, word length, and lexical variation. The results show that audio description scripts in Catalan do hold features typically attributed to easy-to-understand language.